Design Expert System to Identify Student Talent Based on Personality Type Using Certainty Factor Method in SMP Muhammadiyah Kandis Siak Riau Province - Febryanto, Febryanto; Efriyanti, Liza (Knowbase : International Journal of Knowledge in Database, 2022)
The goal of this research is to create a system design that "can assist parents and teachers in recognizing the talents of their students" based on the child's personality, so that parents and teachers can provide "the right education and learning patterns for students". The author discovers that there is no expert system in SMP Muhammadiyah Kandis to identify children's talents based on personality type using certainty factor methods, and that at SMP Muhammadiyah Kandis, evaluations are still done manually and only to determine intelligence, not to determine student talent. The research method that the author uses is the Research and Development method, where the development method that the author uses is the Waterfall method according to Pressman, which the stages consist of Communication, Planning, Modeling, Construction, Development.‎ Based on the findings of the authors' research, the authors were successful in creating this research product, with the functional suitability test results from two experts obtaining a feasibility value of 100%, which was declared Very Fair, and the compatibility test results obtaining a feasibility value of 100%, which was declared Very Eligible and the feasibility score for the usability test was 86.3%, which was declared Very Eligible, and the feasibility score for the material result test was 81%, which was declared Very Eligible, and the feasibility score for the Indonesian linguistic test was 87.5%, which was declared Very Eligible. The aim of this study is to develop a expert system to identify children's interests and talents that are validated and worthy of being operated.